2016
DOI: 10.3389/fonc.2016.00224
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Algorithm to Identify Patients with Multiple Myeloma Using Administrative Claims Data

Abstract: PurposeThe objective was to expand on prior work by developing and validating a new algorithm to identify multiple myeloma (MM) patients in administrative claims.MethodsTwo files were constructed to select MM cases from MarketScan Oncology Electronic Medical Records (EMR) and controls from the MarketScan Primary Care EMR during January 1, 2000–March 31, 2014. Patients were linked to MarketScan claims databases, and files were merged. Eligible cases were age ≥18, had a diagnosis and visit for MM in the Oncology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Our finding that ICD‐9‐CM codes alone are not enough to accurately identify cases of MM is consistent with the work of Princic and colleagues, who found that a combination of multiple diagnoses and laboratory tests or a single diagnosis and chemotherapy was needed to accurately identify MM patients. All Princic algorithms first identified for evaluation potential index MM diagnosis codes as those preceded by >90 days of continuous enrolment and followed by >30 days of continuous enrollment.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our finding that ICD‐9‐CM codes alone are not enough to accurately identify cases of MM is consistent with the work of Princic and colleagues, who found that a combination of multiple diagnoses and laboratory tests or a single diagnosis and chemotherapy was needed to accurately identify MM patients. All Princic algorithms first identified for evaluation potential index MM diagnosis codes as those preceded by >90 days of continuous enrolment and followed by >30 days of continuous enrollment.…”
Section: Discussionsupporting
confidence: 90%
“…During the first stage of the study, we developed, tested, and validated algorithms at HFHS. At the time of algorithm development, there were no published studies of validated algorithms to identify cases of MM in administrative databases (the two previously validated algorithms had not been published). Therefore, we developed algorithms based on previous work, National Comprehensive Cancer Network Guidelines for MM diagnosis, clinical input, and review of patient profiles (chronological summaries of administrative data consisting of diagnosis codes, procedures/tests, and other care received).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[33] However, literature concerning multiple myeloma is very poor, and only one resource could be identified. [34] According to this study, on MarketScan databases linked to Medicare claims databases, at least 2 diagnoses provided a sensitivity of 95%, a specificity of 73%, and a positive predictive value (PPV) of 76%.…”
Section: Discussionmentioning
confidence: 99%